2014
DOI: 10.1152/physiol.00012.2014
|View full text |Cite
|
Sign up to set email alerts
|

Making Microvascular Networks Work: Angiogenesis, Remodeling, and Pruning

Abstract: The adequate and efficient functioning of the microcirculation requires not only numerous vessels providing a large surface area for transport but also a structure that provides short diffusion distances from capillaries to tissue and efficient distribution of convective blood flow. Theoretical models show how a combination of angiogenesis, remodeling, and pruning in response to hemodynamic and metabolic stimuli, termed "angioadaptation," generates well organized, functional networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
93
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 80 publications
3
93
0
5
Order By: Relevance
“…In vascular networks, efficiency is achieved by hierarchical structure and extensive ramification, which together maximize convection and diffusion (Pries and Secomb, 2014). Within these networks, each feeding arteriole gives rise to numerous smaller precapillary arterioles, which in turn drain to venules via even smaller capillary segments.…”
Section: Discussionmentioning
confidence: 99%
“…In vascular networks, efficiency is achieved by hierarchical structure and extensive ramification, which together maximize convection and diffusion (Pries and Secomb, 2014). Within these networks, each feeding arteriole gives rise to numerous smaller precapillary arterioles, which in turn drain to venules via even smaller capillary segments.…”
Section: Discussionmentioning
confidence: 99%
“…The production of a hemodynamically efficient vascular network can occur either by excessive production of blood vessels followed by the pruning of inefficient vessels, or by sprouting of new vessels in hemodynamically efficient locations in the first place. Though vascular networks do overproduce vessels and prune inefficient ones (Pries and Secomb, 2014), this does not negate the possibility of a bias at the site of sprout initiation in perfused vascular networks. It therefore makes physiological sense that the forces created by blood flow could influence the angiogenic process.…”
Section: Introductionmentioning
confidence: 98%
“…Finally, sustained tone influences vascular remodelling, with deep tone being a drive for inward remodelling 23, 24. Previous modelling studies have shown that conducted responses, as important tone regulators, may play a role in vascular structural adaptations 13, 25. Speculatively, conduction of tone could thus result in a smoothing out of irregularities in vascular structure and calibre.…”
Section: Discussionmentioning
confidence: 99%
“…However, coordination of tone is also required at a time scale in the order of minutes to hours. Moreover, modelling studies have shown the importance of conducted responses in structural adaptations in vascular networks13, 14 To the best of our knowledge, only few earlier studies addressed longer lasting stimulation, demonstrating maintenance of conducted vasodilator responses up to two minutes 15, 16. The conduction of vasomotor responses during longer periods has not been studied so far.…”
Section: Introductionmentioning
confidence: 99%